NORMOKALEMIC PERIODIC PARALYSIS IN A 24-YEAR-OLD-FILIPINO MALE WITH GRAVES’ DISEASE - Reburiano, Samantha Bernardine; Lopez, Lizette Kristine (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Thyrotoxic periodic paralysis is a rare event typically presenting with hypokalemia and weakness that occurs primarily among Asians. Rarer still is thyrotoxic periodic paralysis with normokalemia, of which only 6 cases have been reported in the Asian population. There have been no reports of this phenomenon among Filipinos. This is a case of a 24-year-old Filipino male with Graves’ disease on treatment presenting with sudden onset bilateral lower extremity weakness. The patient was treated a week prior with prednisone since he initially exhibited hypersensitivity reactions to methimazole. On the day of the consult, the work-up showed normokalemia, with normal sodium and calcium levels and a suppressed TSH. He was given propranolol and propylthiouracil. Serum potassium monitoring was done. There was no decreased serum potassium levels, hence, the patient was discharged and continued outpatient treatment for hyperthyroidism. This is the first case report of normokalemic thyrotoxic periodic paralysis in the Filipino population.